Enhancing Digital Marketing Skills and Business Innovation to Increase Competitiveness and Household Income of Home-Based Workers - Mesran Mesran; Suginam Suginam; Wardayani Wardayani; Dian Purnama Sari; Rizkah Fadillah; Mohd Imran Bin Ahmad Kamal; Rosnizam Rosnizam; Dodi Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This community service program aimed to enhance digital marketing skills and business innovation among home-based workers in the PPR Seri Sena Community, Kangar, Perlis, Malaysia. The activity was conducted on 13 April 2026 and involved ten participants from the partner community. The program was implemented through a needs assessment, preliminary observation, interviews and discussions with the community, preparation of training materials, an interactive workshop, practical demonstrations, question-and-answer activities, and program evaluation. The training focused on social media utilization, digital marketing, promotional features, digital branding, product differentiation, and business innovation. The evaluation results showed that participants’ understanding of social media utilization for business purposes increased from 44% before the program to 83% after the activity, representing an improvement of 39 percentage points. Understanding of social media promotional features increased from 20% to 75%, representing an improvement of 55 percentage points. These findings demonstrate that participatory and practice-oriented digital marketing training can effectively strengthen the digital competencies of home-based workers and support their readiness to improve business competitiveness. Nevertheless, the program was limited by the small number of participants and the short-term evaluation period, so further mentoring and longitudinal evaluation are recommended to examine its effects on business performance and household income.